Exploring Toxoplasma gondii´s Biology within the Intestinal Epithelium: intestinal-derived models to unravel sexual differentiation - Sena, Florencia; Cancela, Saira; Bollati-Fogolín, Mariela; Pagotto, Romina; Francia, María E. (Frontiers in Cellular and Infection Microbiology, 2023)
A variety of intestinal-derived culture systems have been developed to mimic in vivo cell behavior and organization, incorporating different tissue and microenvironmental elements. Great insight into the biology of the causative agent of toxoplasmosis, Toxoplasma gondii, has been attained by using diverse in vitro cellular models. Nonetheless, there are still processes key to its transmission and persistence which remain to be elucidated, such as the mechanisms underlying its systemic dissemination and sexual differentiation both of which occur at the intestinal level. Because this event occurs in a complex and specific cellular environment (the intestine upon ingestion of infective forms, and the feline intestine, respectively), traditional reductionist in vitro cellular models fail to recreate conditions resembling in vivo physiology. The development of new biomaterials and the advances in cell culture knowledge have opened the door to a next generation of more physiologically relevant cellular models. Among them, organoids have become a valuable tool for unmasking the underlying mechanism involved in T. gondii sexual differentiation. Murine-derived intestinal organoids mimicking the biochemistry of the feline intestine have allowed the generation of pre-sexual and sexual stages of T. gondii for the first time in vitro, opening a window of opportunity to tackling these stages by “felinizing” a wide variety of animal cell cultures. Here, we reviewed intestinal in vitro and ex vivo models and discussed their strengths and limitations in the context of a quest for faithful models to in vitro emulate the biology of the enteric stages of T. gondii.